And this was odd : a light comedy by Kenneth Horne. Criterion Theatre, Piccadilly Circus, W.1. - Horne, Kenneth, 1900-1969.; Criterion Theatre (London, England) ([London] : Criterion Theatre, 1951)
Broadside advertising a production at the Criterion Theatre, Piccadilly Circus, London. Text in red and green on a buff background. "By arrangement with Bronson Albery. In association with Anthony Vivian. John Clements Plays Ltd. presents Mary Jerrold, Raymond Huntley, Avice Landone, Peter Hammond, Joan Harben, Tilsa Page, Elizabeth Henson, Graham Stuart, Mignon O' Doherty ... directed by John Clements, setting by Gower Parks. A.E. King Ltd., 2 Denman Street, London, W.1"
Caption title.
Also available online
Keywords: O'Doherty, Mignon -- Posters; Actresses -- Australia -- Posters; Theatrical posters -- Great Britain; Advertising -- Performing arts -- Great Britain -- Posters; Performing arts -- Great Britain -- Posters; Broadsides -- Great Britain; Great Britain -- Posters